Meningkatkan Hasil Belajar Menulis Resensi Mata Pelajaran Bahasa Indonesia melalui Pendekatan Contextual Teaching and Learning (CTL) Siswa Kelas V SD Negeri 097798 Gaol Tahun Ajaran 2018/2019 - Ficha Aulia Nanda; Dingse Br Silalahi; Ayu Sintya; Oktavianus Rolas Tampubolon (Journal on Education, 2022)
The type of research specified in this research is classroom action research Classroom Action Research (CAR) is an examination in the form of action on learning activities that are intentionally raised and occur in a class simultaneously. The aim is to improve the learning process in improving student learning outcomes through the Contextual Teaching Learning Model. (CTL) The location of this research was carried out at V SD Negeri 097798 Gaol When the research was carried out from September to September 2019 The subjects of this research were fifth grade students at SD Negen 097798 Gaol Academic Year 2018/2019 with a total of 34 students consisting of 18 boys and 16 women. The results of cycle 1, out of 34 students who were the subjects of this study, it turned out that only 21 students (61.76%) already had learning mastery, while the remaining 13 students (38.24%) did not yet have mastery. learning The average value obtained only reached 78.86 Physical Results lus II. It turned out that 32 students (94.11%) already had learning mastery, while the rest, namely 2 students (5.89%) did not have learning mastery. The average value obtained only reached 81.71. Based on this, the conclusion in this research is that there is an increase in the results of learning to review novels through the Contextual Teaching Learning (CTL) Approach in Class V SD Negeri 097798 Gaol Academic Year 2018/2019".